Sex differences in long-term survival and cancer incidence after ruptured abdominal aortic aneurysm repair - Epple, Jasmin; Böckler, Dittmar; Grundmann, Reinhart T. (Journal of Clinical Medicine, 2024)
Background: Long-term gender-specific survival and cancer incidence in patients with ruptured abdominal aortic aneurysm (rAAA) were investigated after endovascular (EVAR) and open repair (OAR). Methods: Data from 2933 patients (EVAR n = 1187, OAR n = 1746) from a health insurance company in Germany (men n = 2391, women n = 542) were analyzed. All patients were cancer-free in their history. Results: Perioperative mortality was significantly higher after OAR (42.6%) than after EVAR (21.2%; p < 0.001). Women had significantly higher in-hospital mortality (41.5%) than men (32.2%). Notably, the 5-year survival was 36.9% after OAR and 40.8% after EVAR (p < 0.001), and 40.7% in men and 29.1% in women (p < 0.001). Overall, 17.2% of EVAR and 14.6% of OAR patients had cancer at 5 years (p = 0.328). Cancer incidence did not differ significantly between men and women. Patients with cancer had a significantly less favorable outcome compared to patients with no cancer (p = 0.002). Treatment of rAAA was also indicated in octogenarians, with survival rates of 19.9% after 5 years and even 38.4% with perioperative deaths excluded. Conclusions: Cancer represents a significant risk factor for survival in patients with rAAA. These patients should be monitored during follow-up, particularly regarding the development of lung cancer.
Gesehen am 12.06.2025